스펙트럼을 이용한 피로손상도 계산과정 최적화 연구 - 김상우(Sang Woo Kim); 이승재(Seung Jae Lee); 최솔미(Sol Mi Choi) (Han-guk haeyang gonghak hoeji (Online), 2018)
Offshore structures are exposed to low- and high-frequency responses due to environmental loads, and fatigue damage models are used to calculate the fatigue damage from these. In this study, we tried to optimize the main parameters used in fatigue damage calculation to derive a new fatigue damage model. A total of 162 bi-modal spectra using the elliptic equation were defined to describe the response of offshore structures. To calculate the fatigue damage from the spectra, time series were generated from the spectra using the inverse Fourier transform, and the rain-flow counting method was applied. The considered optimization variables were the size of the frequency increments, ratio of the time increment, and number of repetitions of the time series. In order to obtain optimized values, the fatigue damage was calculated using the parameter values proposed in previous work, and the fatigue damage was calculated by increasing or decreasing the proposed values. The results were compared, and the error rate was checked. Based on the test results, new values were found for the size of the frequency increment and number of time series iterations. As a validation, the fatigue damage of an actual tension spectrum found using the new proposed values and fatigue damage found using the previously proposed method were compared. In conclusion, we propose a new optimized calculation process that is faster and more accurate than the existed method.